Microbial and Chemical Stability of Unpreserved Atropine Sulfate 0.01% w/w Eye Drops—A Pilot Study on the Impact of Dispenser Type and Storage Temperature over 12 Weeks of Daily Use After Compounding - Klang, Victoria; Brenner, Stefan; Grabner, Johanna; Unzeitig, Philip; Nguyen Hoang, My Vanessa; Lummerstorfer, Maria; Pichler, Roman; Steiner, Katja; Harvey, Richard D. (Life (Basel, Switzerland), 2025)
Progressive myopia in children is a highly prevalent condition in societies worldwide and is often treated with compounded low-dose atropine sulfate (AS) eye drops without preserving agents to avoid irritation/sensitisation. Surprisingly, there is a lack of data regarding the in-use stability of contamination-free LDPE dispenser units (CFDs) for this compounded multidose product, which causes uncertainty among prescribers and patients in Europe. Thus, our aim was to compare the effect of different dispenser types on the chemical and microbial stability of unpreserved AS eye drops (0.01% w/w). A dripping simulation was performed to obtain information on microbial stability over 4 weeks through plating and separately over 12 weeks through direct inoculation, HPLC and pH analysis. For CFDs, no contamination was found after 4, 8 or 12 weeks of use when stored at 23 or 4 °C as opposed to the control. AS content remained within 0.01 ± 0.0002% w/w after 12 weeks, with higher chemical stability at 4 °C despite decreasing pH. A stress test confirmed the validity of the CFD system. In conclusion, using CFDs and refrigerated storage was found to be safe for compounded unpreserved AS eye drops over 12 weeks of use.